Enhancing Research Visibility in Africa: Leveraging DOAJ for Open Access Publishing - Smith, Ina (My University, 2024)
Enhancing Research Visibility in Africa: Leveraging DOAJ for Open Access Publishing - AfricArXiv Open Science Webinar Series 2024
This webinar session featured Ina Smith, the Planning Manager, Scholarly Publishing Unit, Academy of Science of South Africa (ASSAf), South Africa & DOAJ Ambassador Southern Africa. She spoke on the topic: Enhancing Research Visibility in Africa: Leveraging DOAJ for Open Access Publishing. Attendees learned how African researchers and journals can increase their visibility and impact through DOAJ. Key points highlighted: – How to get your research and journals listed in DOAJ – The benefits of open-access publishing for African scholars – Strategies for overcoming common challenges in open access This webinar series is co-organized by: UbuntuNet Alliance and Access 2 Perspectives as part of the ORCID Global Participation Program: https://info.orcid.org/global-participation-program/
Keywords: Open Science; Open Access; Research; African Research; DOAJ